Strategi Membangun Budaya Positif Untuk Kesuksesan Peserta Didik di SMAN 5 Palangka Raya - Andi Indah Jayanti; Andia Misy; Dhani Susilowati; Misnawati Misnawati; Olga Dona Retsi; Patrisia Cuesdeyeni; Albertus Purwaka; Linggua Sanjaya Usop; Devina Putri; Icha Fina Fanesha; Ivan Qoriul Amrin (Universitas Palangka Raya, 2025)
The culture of the five elite imposes discipline and cultural values upon learners. This study aims to (1) describe the School Culture at SMAN 5 Palangka Raya, (2) describe the Factors Affecting School Culture at SMAN 5 Palangka Raya, (3) describe the School Culture Development Strategy at SMAN 5 Palangka Raya, (4) Describe the Influence of School Culture on the Success of Students at SMAN 5 Palangka Raya. The study USES qualitative descriptive methods. The object of this study is the culture of SMAN 5 Palangka Raya, while the research subject consists of school residents, including teachers, trainees, and staff involved in everyday school life. The result was that SMAN 5 Palangka Raya focused on developing character learners like discipline through activities such as prayer, morning apples, and march lines. It also excelled in achievement, provided full facilities, and offered extracurriculars. Parental leadership, roles, and support play an important role in creating a positive culture. For further development, it needs to be reinforced in positive values, innovative learning methods, extracurriculars, facilities, and parental and child-friendly school programs to create a safe and inclusive environment. These cultures are what led to the success of the elite SMAN 5 Palangka Raya elite trainees to college and service.